2001
DOI: 10.1097/00009957-200101000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Dislocation of the Thoracic Spine: Case Report and Review of the Literature

Abstract: A fracture dislocation of the upper thoracic spine with spinal cord injury is reported in a neonate. This rare injury is associated with attendant predisposing obstetric circumstances (breech transverse presentations, large baby size) that can alert clinicians of potential problems and aid in the diagnosis of neonatal hypotonia and paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Although the precise contemporary incidence is difficult to estimate, they are thought to occur in about 1/80,000 live births [3, 4]. Recently, there has been greater awareness of this diagnosis on the part of neonatologists, pediatric neurologists and neurosurgeons [5, 6]. Prior to this, the diagnosis was rarely considered and frequently missed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the precise contemporary incidence is difficult to estimate, they are thought to occur in about 1/80,000 live births [3, 4]. Recently, there has been greater awareness of this diagnosis on the part of neonatologists, pediatric neurologists and neurosurgeons [5, 6]. Prior to this, the diagnosis was rarely considered and frequently missed.…”
Section: Discussionmentioning
confidence: 99%
“…The review by McKinnon et al [3]of 22 neonates with birth-related spinal injuries demonstrated that 14/22 had rostral cervical spine injuries and that all had a cephalic presentation. Those with cervicothoracic injuries were most commonly the result of a breech presentation [5]. The mechanism of injury differs between infants who present with breech and cephalic presentation [5, 7, 8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,26 The primarily cartilaginous vertebral bodies in newborns do not interlock snugly to provide the same degree of protection as those of older infants. 8,26 Hypotonia exaggerates the risk of injury secondary to laxity of the supporting muscles. Any neuromuscular condition that reduces muscle tone increases the risk of SCI because these conditions allow increased stretch of the vertebral column during delivery.…”
Section: Development Of the Fetal Spinementioning
confidence: 99%
“…2,3 The incidence is estimated to be 1 in 80,000 live births 4 ; SCIs have been documented on neonatal postmortem studies in 10% to 14.9% of cases that included evaluation of the spinal cord. 2,[5][6][7][8][9][10] Obstetrical manipulations at or around birth, such as traction or rotation, escalate the risk of SCI. 6,11 Advances in diagnostic imaging that improve the accurate estimation of fetal size and presentation and the use of cesarean birth to avoid difficult deliveries has reduced the incidence of SCI related to obstetrical maneuvers.…”
mentioning
confidence: 99%